PERAN STRATEGI SUPERVISI AKADEMIK DAN KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN PROFESIONALISME GURU SD - Lulah Natalia; Tri Widayatsih; Mahasir Mahasir (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
This study examines the role of academic supervision strategies and principal leadership in improving teacher professionalism at SD Negeri 167 Palembang, where challenges include misalignment in lesson planning, limited innovation in teaching methods, and low participation in professional development due to administrative burdens and insufficient humanistic supervision. The study aims to describe academic supervision strategies, leadership styles, supporting and inhibiting factors, and teachers’ perceptions of these roles. A qualitative approach was employed using in-depth interviews, participant observation (pre-observation, classroom observation, and post-observation), and document analysis such as lesson plans and supervision reports. Data validity was ensured through source triangulation involving the principal, vice principal for curriculum, and 18 teachers. The findings reveal that the principal implements clinical supervision based on coaching and mentoring through three stages: pre-observation (socialization), observation (focusing on teacher–student interaction and digital media use), and post-observation (reflective feedback and internal workshops). This is supported by a democratic, participatory, empathetic, and instructional leadership style. Supporting factors include teacher commitment, collaborative culture, and adequate facilities, while inhibiting factors involve administrative workload, time constraints, discomfort during supervision, and inconsistent follow-up. Teachers perceive this humanistic approach positively as it enhances pedagogical competence, motivation, and performance. In conclusion, responsive academic supervision and leadership function as a systemic approach to fostering sustainable teacher professionalism and a progressive school culture. ABSTRAK Penelitian ini mengkaji peran strategi supervisi akademik dan kepemimpinan kepala sekolah dalam meningkatkan profesionalisme guru di SD Negeri 167 Palembang. Permasalahan yang dihadapi meliputi ketidaksesuaian perencanaan pembelajaran, minimnya inovasi metode mengajar, serta rendahnya partisipasi guru dalam pengembangan profesional akibat beban administrasi dan kurangnya supervisi yang humanis. Penelitian ini bertujuan untuk mendeskripsikan strategi supervisi akademik, gaya kepemimpinan kepala sekolah, faktor pendukung dan penghambat, serta persepsi guru terhadap peran tersebut. Penelitian menggunakan pendekatan kualitatif dengan teknik pengumpulan data melalui wawancara mendalam, observasi partisipan (pra-observasi, observasi kelas, dan pasca-observasi), serta analisis dokumen seperti RPP dan laporan supervisi. Keabsahan data dijamin melalui triangulasi sumber yang melibatkan kepala sekolah, wakil kurikulum, dan 18 guru. Hasil penelitian menunjukkan bahwa kepala sekolah menerapkan supervisi klinis berbasis coaching dan mentoring melalui tiga tahapan, yaitu pra-observasi, observasi, dan pasca-observasi. Strategi ini didukung oleh gaya kepemimpinan demokratis, partisipatif, empatik, dan berorientasi instruksional. Faktor pendukung meliputi komitmen guru, budaya kolaborasi, dan fasilitas yang memadai, sedangkan faktor penghambat mencakup beban administrasi, keterbatasan waktu, serta tindak lanjut yang belum konsisten. Kesimpulannya, supervisi akademik dan kepemimpinan yang responsif menjadi pendekatan sistemik dalam meningkatkan profesionalisme guru secara berkelanjutan.